2019
DOI: 10.1590/1980-265x-tce-2018-0073
|View full text |Cite
|
Sign up to set email alerts
|

Dressings Indicated in the Treatment of Mediastinitis After Cardiac Surgery: Integrative Review

Abstract: Objective: identify and describe which dressings are recommended in the treatment of mediastinitis after cardiac surgery in adult patients. Method: integrative review held in the databases MEDLINE/PubMed, LILACS, CINAHL, Web of Science, Cochrane, SCOPUS and manual search, between December 2017 and January 2018. It was selected studies on dressings used in the treatment of mediastinitis after cardiac surgery. Results: eight articles were included: three addressed the treatment of negative pressure wounds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
(111 reference statements)
0
2
0
2
Order By: Relevance
“…It is noteworthy that a recent integrative review analyzing eight retrospective observational studies comparing the use of NPWT with conventional dressings to treat mediastinitis concluded that NPWT was superior to other technologies. NPWT contributed to increased healing speed and low rates of reinfection, mortality or hospital readmission (23) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is noteworthy that a recent integrative review analyzing eight retrospective observational studies comparing the use of NPWT with conventional dressings to treat mediastinitis concluded that NPWT was superior to other technologies. NPWT contributed to increased healing speed and low rates of reinfection, mortality or hospital readmission (23) .…”
Section: Discussionmentioning
confidence: 98%
“…The World Health Organization (WHO) recommends only prophylactic use of NPWT to prevent SSI in previously closed, high-risk surgical incisions (22) . However, it is observed in clinical practice that the most frequent use of this technology is related to the treatment of SSI, although its use is supported by limited scientific evidence, especially for the treatment of SSI after cardiac surgery (23) . For this reason, its indication should be cautious due to the expensive device-related costs and the low quality of evidence (22) , leading to the need to explore the clinical outcomes of patients undergoing NPWT SSI treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo dia de pós operatório. Ferida sem sinais de sofrimento isquêmico, em bom aspecto profundidade da lesão etc (16,17) . Em um estudo realizado com 69 pacientes com mediastinite por esternotomia foi realizado o curativo em questão contra 49 pacientes que foram submetidos a tratamento convencional.…”
Section: Discussionunclassified
“…Observou-se de forma estatisticamente significativa que houve diminuição da taxa de mortalidade e da taxa de re-infecção no grupo que fez uso da terapia de pressão negativa (3) . Outro estudo realizado também entre 2018 -2019 nas bases de dados MEDLINE/PubMed, LILACS, CINAHL, Web of Science, Cochrane e SCOPUS sobre o mesmo tema também corrobora os mesmos resultados, indicando diminuição da mortalidade e de re-infecção da ferida (16) Portanto, conclui-se que a terapia por pressão negativa funciona como um mecanismo de ponte para acelerar a recuperação da ferida e diminuir suas complicações. No caso da mediastinite deve ser associada a antibioticoterapia guiada e múltiplos debridamentos em conjunto.…”
Section: Discussionunclassified
“…A evolução na área de tratamento de feridas tem sido um evento complexo e dinâmico (Colares et al, 2019). Existe uma diversidade de pensos com diferentes ações terapêuticas, de modo a favorecer a granulação e epitelização dos tecidos (Frantz et al, 2019).…”
Section: Introductionunclassified